Efeito de diferentes dietas sobre o desenvolvimento pós- embrionário de Chrysoperla defreitasi Brooks (Neuroptera: Chrysopidae) - Biagioni, Alexandre [UNESP]; De Freitas, Sérgio [UNESP] (My University, 2001)
The post-embryonic period of the predator Chrysoperla defreitasi Brooks, fed on eggs of Sitotroga cerealella (Olivier) and Diatrea saccharalis (Fabricius) was evaluated under laboratory conditions at 25±2°C temperature, 70±10% RU, and 14h photophase. The chrysopidae eggs were individualized in glass tubes and after eclosion the larvae were fed on the respective preys and maintained under controlled conditions in a climatic chamber. The experimental design used was completely randomized with 150 replications for each diet. The duration of the 1st, 2nd, and 3rd instars as well as of the pupal phase were 3.4, 2.7, 3.5, and 11.9 days, respectively, for the larvae fed on D. saccharalis and 3.6, 2.8, 2.7, and 9.3 days, respectively, when the diet provided was S. cerealella eggs. Chrysopidae larvae fed on eggs of D. saccharalis took an average of 21.5 days to complete the post-embryonic development, with 34.0% of adults emerged, while the individuals fed on S. cerealella eggs took 18.4 days in average, with 55.3% of adults emerged. Data allowed to conclude that the best diet for post-embryonic development of C. defreitasi are eggs of S. cerealella, since insects fed on that diet had a shorter development period, higher viability of the three larval instars as well as of the pupal stage, producing higher number of adults.
Effect of different diets on post-embryonic development of Chrysoperla defreitase Brooks (Neuroptera: Chrysopidae)
Keywords: Biology; Chrysopidae; Diet; Insecta